2018
DOI: 10.1002/pssa.201700655
|View full text |Cite
|
Sign up to set email alerts
|

High‐Power Microwave GaN/AlGaN HEMTs and MMICs on SiC and Silicon Substrates for Modern Radio Communication

Abstract: In this paper the recent use AlGaN/GaN high electron mobility transistors (HEMTs) and integrated circuits on both semi‐insulating silicon carbide (SiC) and silicon substrates for radio communication in the microwave and mm‐wave frequency range is described. AlGaN/GaN monolithically microwave integrated circuits (MMICs) are extremely useful for point‐to‐point (P2P)‐links in the backbones of the 4th and upcoming 5th generation of mobile communication networks as power amplifiers, as they provide a great amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…There are several reports on GaN-on-Si power amplifier ICs at millimeter-wave frequencies: a Ka-band 8 W power amplifier in 100-nm GaN HEMT [9], a 40 GHz 12 W power amplifier with a PAE of 30% at 40 GHz (power density of 3.2 W/mm) [10], and a W-band power amplifier in 50 nm GaN HEMT producing output power of 18.3 dBm with power density of 1.35 W/mm at 94 GHz [11]. It can be concluded that the reported GaN-on-Si power amplifiers exhibit the inferior performance to GaN-on-SiC technologies at all frequencies [8]. The performance gap widens at higher frequencies like the W-band.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…There are several reports on GaN-on-Si power amplifier ICs at millimeter-wave frequencies: a Ka-band 8 W power amplifier in 100-nm GaN HEMT [9], a 40 GHz 12 W power amplifier with a PAE of 30% at 40 GHz (power density of 3.2 W/mm) [10], and a W-band power amplifier in 50 nm GaN HEMT producing output power of 18.3 dBm with power density of 1.35 W/mm at 94 GHz [11]. It can be concluded that the reported GaN-on-Si power amplifiers exhibit the inferior performance to GaN-on-SiC technologies at all frequencies [8]. The performance gap widens at higher frequencies like the W-band.…”
Section: Introductionmentioning
confidence: 90%
“…It is worthwhile to emphasize that the W-band power amplifier ICs mentioned above are based on GaN on silicon carbide (SiC) HEMT technologies [1][2][3][4][5][6][7], where a GaN channel is grown on the SiC substrate with a buffer layer in between [4]. They present the superior performance to GaN-on-Si HEMTs, which are grown on the Si substrate, in terms of output power, power density, and PAE at all frequency ranges [8]. The SiC substrate also exhibits lower loss and better thermal conductivity compared to the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Field effect high electron mobility transistors (HEMTs) with two-dimensional electron gas (2DEG) are widely utilized as high-speed active elements of microelectronic devices [1][2][3][4]. There are often reports on new records regarding the improvement of their technology and the launch of new structures.…”
Section: Introductionmentioning
confidence: 99%
“…The GaN exhibits high breakdown voltage characteristics derived from the wide gap structure, and it is possible to exhibit an output exceeding 1 A in the HEMT structure [3]. Extant studies investigated the application of GaN-HEMTs to green ICT systems as high efficiency devices [4]. The device structure of GaN-HEMT is constructed with a superlattice structure of AlGaN and i-GaN.…”
Section: Introductionmentioning
confidence: 99%